2015
DOI: 10.1128/mbio.01390-15
|View full text |Cite|
|
Sign up to set email alerts
|

Fatal Pediatric Cerebral Malaria Is Associated with Intravascular Monocytes and Platelets That Are Increased with HIV Coinfection

Abstract: Cerebral malaria (CM) is a major contributor to malaria deaths, but its pathophysiology is not well understood. While sequestration of parasitized erythrocytes is thought to be critical, the roles of inflammation and coagulation are controversial. In a large series of Malawian children hospitalized with CM, HIV coinfection was more prevalent than in pediatric population estimates (15% versus 2%, P < 0.0001, chi-square test), with higher mortality than that seen in HIV-uninfected children (23% versus 17%, P = 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(98 citation statements)
references
References 73 publications
2
91
4
1
Order By: Relevance
“…As EPCR plays a central role in vascular homeostasis by facilitating the activation of the plasma protease protein C to activated protein C (APC) (Mosnier et al, 2007), it has been hypothesized that parasites may potentiate cerebral vascular dysfunction by inhibiting the protective APC-EPCR interaction (Gillrie et al, 2015; Petersen et al, 2015; Turner et al, 2013). Indeed, pediatric CM brain autopsies have revealed alterations in coagulation (fibrin deposits and platelet infiltrates) (Dorovini-Zis et al, 2011; Grau et al, 2003; Hochman et al, 2015; Moxon et al, 2015) and increased BBB permeability (Brown et al, 2001; Dorovini-Zis et al, 2011). However, the specific contribution of the CIDRα1-EPCR interaction to late stage disease mechanisms important for CM pathogenesis or fatality has been largely unaddressed.…”
Section: Introductionmentioning
confidence: 99%
“…As EPCR plays a central role in vascular homeostasis by facilitating the activation of the plasma protease protein C to activated protein C (APC) (Mosnier et al, 2007), it has been hypothesized that parasites may potentiate cerebral vascular dysfunction by inhibiting the protective APC-EPCR interaction (Gillrie et al, 2015; Petersen et al, 2015; Turner et al, 2013). Indeed, pediatric CM brain autopsies have revealed alterations in coagulation (fibrin deposits and platelet infiltrates) (Dorovini-Zis et al, 2011; Grau et al, 2003; Hochman et al, 2015; Moxon et al, 2015) and increased BBB permeability (Brown et al, 2001; Dorovini-Zis et al, 2011). However, the specific contribution of the CIDRα1-EPCR interaction to late stage disease mechanisms important for CM pathogenesis or fatality has been largely unaddressed.…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies in pediatric patients have revealed the presence of some monocytes and platelets in the cerebral microvascular. 17,27,29 There is also a suggestion that there may be systemic neutrophil activation which may contribute to cerebral pathology through soluble mediators such as myeloperoxidase and elastase that are released. 30 In contrast to the findings in the brain, features consistent with acute lung injury are frequently found in the pulmonary microvasculature at autopsy of both adult and pediatric patients with severe falciparum malaria.…”
Section: Clinical Evidence Of Barrier Dysfunction In Severe Malariamentioning
confidence: 99%
“…In P. falciparum-infected patients with CM, massive iRBC cytoadherence is observed in the brain microvasculature (Silamut et al 1999;Milner et al 2014). The intravascular presence of leukocytes in the brain has long been debated; however, an increasing number of recent papers clearly show the presence of monocytes and platelets on brain autopsies from fatal CM patients alongside with iRBCs (Patnaik et al 1994;Hochman et al 2015). In mice with experimental CM, brain microvascular obstruction is mainly mediated by cytoad-…”
Section: Excessive Irbc Sequestrationmentioning
confidence: 99%
“…However, P. falciparum and P. vivax patients with severe malaria infections have significantly reduced ADAMTS13-activity (de Mast et al 2009;Larkin et al 2009;Lowenberg et al 2010;Barber et al 2015). Thus, the combination of endothelial activation with increased circulating amounts of active and UL-vWF, together with reduced vWF inactivation by ADAMTS13, may result in intravascular platelet aggregation, as observed in brains and lungs of severely ill patients and mice (Grau et al 1993(Grau et al , 2003Sun et al 2003;Wassmer et al 2004;von Zur Muhlen et al 2008;Hochman et al 2015) and in P. falciparum-infected placentas (Wassmer et al 2004). In P. vivax patients, platelet numbers are also positively correlated with ANG1 and negatively with ANG2 and the ANG2/ANG1 ratio .…”
Section: Coagulation Changesmentioning
confidence: 99%
See 1 more Smart Citation